Aforizmlar lingvistik tadqiqot obyekti aphorisms are the object of linguistic research - Samiyeva Nilufar Baxtiyorjon qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
In this article, the essence of aphorisms, their emergence in Uzbek and world linguistics, as well as their structural-grammatical and functional-semantic features were analyzed on the basis of evidence. Also, the views of linguists about aphorisms are thoroughly analyzed.